Clinical Association Factors for Abnormal Cranial CT Scan in Moderate-Risk Patients of Mild Traumatic Brain Injury - Watcharakorn, Arvemas; Romsaiyut, Tanaphat; Amnuaypattanapon, Kumpol; Mingkwansook, Varalee (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Moderate-risk patients with mild traumatic brain injury have not needed routine cranial CT scans. The management can be observed after presentation or undergoing a cranial CT scan. A cranial CT scan in this group is warranted in selected cases. This study aims to find clinical association factors for abnormal cranial CT scan in moderate-risk patients of mild traumatic brain injury for identifying the patients who may need a cranial CT scan to reduce unnecessary cranial CT scans and the cost of treatment. Objective: This study’s purpose is to evaluate clinical association factors for abnormal cranial CT scan in moderate-risk patients of mild traumatic brain injury. Methods: Data of moderate-risk patients with mild traumatic brain injury of Thammasat University Hospital with age ≥ 18 years and ≤ 64 years who underwent a cranial CT scan within the first 24 hours after the onset of the injury were collected. Multivariable logistic regression was used to determine positive CTs’ adjusted odds ratio (OR). Results: Of all 225 patients, 134 (59.6%) had negative cranial CT findings, and 91 (40.4%) had positive cranial CT findings. There were three independent clinical presentations associated with abnormal cranial CT findings including GCS, vomiting and post-traumatic amnesia, the adjusted OR (95% CI) of which were 2.32 (1.04-5.20) (P-value = .040), 4.86 (1.04-22.69) (P-value = .045) and 2.30 (1.12-4.35) (P-value = .010), respectively. Conclusions: Clinical association factors for abnormal cranial CT scan in moderate-risk patients of mild traumatic brain injury, including GCS lower than 15, vomiting, and post-traumatic amnesia.